Taking stock of our journal's journey: A statement of impact - Fields A; Hartnett M (Flexible Learning Association of New Zealand (FLANZ))
Pausing to take stock of progress on a journey can achieve many things, including identifying how far you’ve come, which way you’ve come, and which way you want to go. A statement of impact for the Journal of Open, Flexible and Distance Learning (JOFDL) has been prepared, taking stock of the Journal at the current time in its journey. This statement identifies the Journal and its impact in terms of reach, use, and contribution to global academic research and publishing. The Editorial is rounded off with an overview of the articles in this issue.
Keywords: journal metrics; open learning; statement of impact